Resistance status of main malaria vector, Anopheles stephensi Liston (Diptera: Culicidae) to insecticides in a malaria Endemic Area, Southern Iran - Madineh Abbasi; Ahmad Ali Hanafi-Bojd; Mohammad Reza Yaghoobi-Ershadi; Hassan Vatandoost; Mohammad Ali Oshaghi; Teimour Hazratian; Mohammad Mehdi Sedaghat; Sajjad Fekri; Reza Safari; Abdol Rasoul Mojahedi; Yousef Salari (Asian Pacific Journal of Tropical Medicine, 2019)
Objective: To evaluate the susceptibility of Anopheles stephensi (An. stephensi) Liston, the main malaria vector in southern Iran, to WHO recommended insecticides. Methods: Larvae of An. stephensi were collected from three different larval habitats in both urban and rural area of Bandar Abbas city and one rural area in Rudan county southern Iran. WHO standard method was used for evaluation of adult and larval mosquito susceptibility. Bendiocarb, permethrin, lambda-cyhalothrin, deltamethrin as insecticide and temephos and chlorpyriphos as larvicide were used at the diagnostic dosages recommended by WHO. Results: Findings of this study showed all larval populations of An. stephensi were completely susceptible to temephos and candidate for resistance to chlorpyriphos. Adult mosquitoes in rural areas of Bandar Abbas city were resistant to pyrethroid and carbamate insecticides. Conclusion: Comparison of the results of this survey with previous studies indicates that the resistance to pyrethroids and carbamates in this malaria endemic region is increasing. Wide use of pesticides in agriculture is certainly effective in increasing resistance. The inter-sectoral coordination and collaboration in health and agriculture seem to be necessary to manage insecticide resistance in malaria vectors.